Modification of Gold Electrodes with Bacterial Reaction Centres Immobilized by Laser Induced Forward Transfer (LIFT) Technique for Amperometric Herbicide Detection. (2017) - Guascito, M.R.; Chatzipetrou, M.; Chirizzi, D.; Trotta, M.; Massaouti, M.; Giotta, L.; Milano, F.; Zergioti, I.
Abstract: The functionalization of screen-printed electrodes (SPEs) with a thin film of reaction centre (RC) proteins from the phototrophic bacterium Rhodobacter (R.) sphaeroides, by means of laser induced forward transfer (LIFT) technique, allowed the fabrication of robust and sensitive bio-hybrid devices for terbutryn detection and analysis. The optimal wiring between RCs and the gold electrode surface, achieved by LIFT, led to the generation of cathodic photocurrents sustained by a direct electron transfer (DET) mechanism, which were attenuated by addition of the herbicide inhibitor.